Catalytic supercritical water oxidation of wastewater from terephthalic acid manufacturing process - Park, TJ; Lim, JS; Lee, YW; Kim, SH (ELSEVIER SCIENCE BV, 2003)
Catalytic oxidation of wastewater from terephthalic acid manufacturing plant has been accomplished in supercritical water. All experiments were performed in an isothermal tubular reactor at pressures from 220 to 300 bar, and temperatures from 418 to 513 degreesC. A commercial bulk gamma-Al2O3 was used as a catalyst in a tubular reactor. At reactor entrance, the initial chemical oxygen demand (COD) concentrations of the wastewater were between 3.99 x 10(-3) and 2.81 x 10(-2) M: the COD concentrations of wastewater in feed tank were between 2400 and 14917 ppm. The oxygen concentrations at reaction conditions were between 1.4 x 10(-3) and 7.4 x 10(-3) M, which were the stoichiometric amount needed to oxidize wastewater completely to carbon dioxide. As a result of experiment, the conversion of wastewater was increased with higher wastewater feed concentration, the oxygen concentrations and contact times, and the power-law rate expression that best correlates the experimental results for the conversion of COD to CO2 is rate = -2.67 x 10(2) exp(-55.456/RT)[COD](0.18)[O-2](0.49). (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: KINETICS; PHENOL